2000
DOI: 10.1128/iai.68.12.6602-6610.2000
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Signaling Pathways Leading to Ca2+and Cyclic AMP Elevation in Host Cell Invasion byTrypanosoma cruzi

Abstract: Cell invasion by the protozoan parasite Trypanosoma cruzi involves activation of host signaling pathways and the recruitment and fusion of lysosomes at the parasite entry site. A major signaling pathway regulating invasion of fibroblasts, epithelial cells, and myoblasts involves mobilization of Ca 2؉ from intracellular stores and requires the activity of a T. cruzi serine peptidase, oligopeptidase B (OPB). Deletion of the OPB gene results in a marked defect in trypomastigote virulence, consistent with a greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 35 publications
1
59
0
3
Order By: Relevance
“…Thus, our data do not support gross underrepresentation of lysosome-associated parasites. Moreover, the existence of a significant, lysosome-independent route for T. cruzi entry may offer an explanation for previous observations showing that interference with the function of synaptotagmin VII, an important component of Ca 2+ -regulated lysosome exocytosis machinery (Reddy et al, 2001), resulted in an ~90% inhibition of Ca 2+ -dependent lysosome exocytosis (Martinez et al, 2000), while the effect on T. cruzi invasion was considerably less profound (Caler et al, 2000).…”
Section: Discussionmentioning
confidence: 80%
“…Thus, our data do not support gross underrepresentation of lysosome-associated parasites. Moreover, the existence of a significant, lysosome-independent route for T. cruzi entry may offer an explanation for previous observations showing that interference with the function of synaptotagmin VII, an important component of Ca 2+ -regulated lysosome exocytosis machinery (Reddy et al, 2001), resulted in an ~90% inhibition of Ca 2+ -dependent lysosome exocytosis (Martinez et al, 2000), while the effect on T. cruzi invasion was considerably less profound (Caler et al, 2000).…”
Section: Discussionmentioning
confidence: 80%
“…cAMP is an important signalling molecule regulating various cellular functions, including virulence factors from a diverse range of pathogens (Alspaugh et al, 2002;Caler et al, 2000;D'Souza & Heitman, 2001;Gross et al, 2003;Lee et al, 2003;Li et al, 2002). There is little information about the role of cAMP in mycobacteria, despite its presence in both fast-and slow-growing, as well as pathogenic and nonpathogenic, species (Padh & Venkitasubramanian, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…In most of the studies such interference is negative, decreasing the rate of infection and increasing attachment (Barbosa et al, 1995;Meirelles et al, 1982). In other situations, however, it has been shown that cytochalasin treatment even enhances parasite penetration (Caler et al, 2000;Nogueira et al, 1976;Procopio et al, 1994;Schenkman et al, 1991;Sibley et al, 2000). We decided to re-investigate the problem using cytochalasin D in concentrations described for other systems and which proved to be highly effective at a concentration of 5 µg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out by several groups have shown that involvement of host cell actin with cytochalasins interferes with the internalization of trypomastigote forms into vertebrate cells (Barbosa et al, 1995;Burleigh et al, 1995;Burleigh et al, 1998;Caler et al, 2000;Carvalho et al, 1999;Mortara et al, 1999;Nogueira et al, 1976;Procopio et al, 1994;Schenkman et al, 1991). In most of the studies such interference is negative, decreasing the rate of infection and increasing attachment (Barbosa et al, 1995;Meirelles et al, 1982).…”
Section: Discussionmentioning
confidence: 99%